(untitled) (Baghdad Science Journal, 2009)
The result showed that hot water and ethanol extracts of Nigella sativa contain alkaloids ,saponins, flavonoids,tannins,glycosides,terpins and steroids. Albino mice were administered orally with 0.1 of the extract at dose of 100 mg/kg, body weight the results showed high level of white blood cell ,total and differential count of WBC,phagocytosis index, mitotic index, Arthus and delayed type hypersensitivity. The result, also showed high level of hemoglobin (Hb) and the packed cell volume (PCV) the alcoholic extract has been found more efficient than hot water extract on mice.